2017
DOI: 10.1515/pcard-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up on 107 Fetuses with Normal Us + Echo After 37TH Week of Gestation

Abstract: Introduction: Echocardiography of the fetal heart is an ultrasound examination that allows the evaluation of the anatomical structure and cardiovascular system usually performed in first half of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The possible beneficial effects of transplacental digoxin therapy are discussed. The literature consists of a small number of cases showing an attempt to reduce the progression of cardiomegaly and improve the contractility of the heart in the case of fetal Ebstein's anomaly [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible beneficial effects of transplacental digoxin therapy are discussed. The literature consists of a small number of cases showing an attempt to reduce the progression of cardiomegaly and improve the contractility of the heart in the case of fetal Ebstein's anomaly [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…At this point the authors would like to highlight the special importance of fetal heart and cardiovascular system examination. One of the methods of fetal monitoring is targeted echocardiography, which, with high probability, predicts normal fetal development before and after delivery [21]. Fetal echocardiographic examination contains basic obstetrical screening in addition to elaborate cardiovascular assessment (Table 3) [22].…”
Section: Separate Elements Of Examinationmentioning
confidence: 99%
“…We also would like to underline the value of prenatal detailed echocardiography evaluation in 3rd trimester. There was normal heart anatomy and no functional abnormalities which allowed to assume no necessity for premature delivery and good clinical outcome of the newborn baby without respiratory or heart problems 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, if the fetus is monitored using fetal echocardiography over a period of several weeks, and the last examination is performed shortly before delivery, the condition of the newborn in the first hours and days of extrauterine life can be reliably predicted [1,2,16]. On the basis of the analysis of echocardiographic examinations of 107 fetuses, Strzelecka et al demonstrated, that if the anatomy and function of the fetal heart was evaluated as normal at the 37 th week of pregnancy or later, the newborn would be born in good general condition in each case [17]. The most important objectives of fetal echocardiography in the third trimester of uncomplicated pregnancy are listed below and will be discussed in detail later in the text:…”
Section: The Rationale and Goals Of Fetal Echocardiography In The Thimentioning
confidence: 99%